Prevenção através do projeto : estudo de boas práticas na indústria da construção civil - Martins, João Gabriel Santos (2023)
The civil construction industry plays a significant role in the economic and social aspects of the country. Linked to this, it is responsible for high rates of accidents at work and is considered one of the most dangerous industries. The scientific literature shows that projects may be related to the occurrence of these accidents. Therefore, designers can contribute to the reduction of these rates through the concept of prevention through design (PtD), which consists of anticipating and eliminating safety risks to the worker in the design phase, in order to avoid the occurrence of accidents at work throughout the life of a building. The literature on PtD in Brazil reveals the lack of studies that address this issue and, specifically, the implementation of PtD in the civil construction industry, revealing that this is a promising area for research. Thus, the present study sought to investigate the use of PtD in building projects in civil construction companies. A systematic review of the literature was carried out and 58 good PtD practices were identified, as well as 13 potential barriers that could hinder its adoption. A case study was also carried out in six construction companies that operate in the buildings subsector. With the case study, it was possible to observe among the cases that the construction companies already use some of the good PtD practices, even if unconsciously. It was also found that the use of good practices would be, for the most part, important to prevent risks to worker safety and that the phase of the construction cycle most impacted by the use of good practices would be the execution phase. As for the barriers, it was noted that the designers' lack of knowledge about the impact of design decisions on construction safety, the lack of knowledge about worker safety among designers and the lack of knowledge about PtD design practices by designers can potentially affect the use of the PtD in the construction companies analyzed. From this study, it is expected to contribute to the advancement of knowledge about PtD in the scientific literature by making available the list of good PtD practices and serve as a reference for builders and professionals in the construction industry to consider the safety of the worker in their projects and are aware of the influence that design decisions have to impact safety conditions in work situations.